Corporate governance and Corporate Social Responsibility in Islamic Banking: The case of the Moroccan banks in Italy - Ait Allali, Asma (European Journal of Islamic Finance, 2016)
This paper aims to analyze the model of the Islamic bank with a business economics perspective. In particular, the author analyzes the topic of corporate governance in the Islamic bank. Starting with an overall analysis of the peculiarities and religious principles underlying the model of the Islamic Bank, as well as the similarities present in the field of Corporate Social Responsibility, we will address the theoretical aspect of corporate governance, the relationship between corporate governance and the Islamic bank stakeholders with specific regard to the possible connotations of the active or passive role of savers and investors in the decisions of management and governance related to the selected projects and funding recipients. Finally, given the current absence of Islamic banks in Italy, we propose a case study concerning the possible introduction of Islamic Shari’ah-compliant financial products by Moroccan banks operating in Italy, after the introduction of the recent Moroccan law n° 103.12, approved on 25 November 2014, relating to the credit institutions, envisages the establishment of “Participative Banks” and the offering of Shari’ah-compliant financial products.